2019
DOI: 10.1111/bjso.12362
|View full text |Cite
|
Sign up to set email alerts
|

Shared social identification in mass gatherings lowers health risk perceptions via lowered disgust

Abstract: Previous research concerning mass gathering-associated health risks has focused on physical factors while largely neglecting the role of psychological factors. The present research examined the effect of experiencing shared social identification on perceptions of susceptibility to health risks in mass gatherings. Participants in Study 1 were asked to either recall a crowd in which they shared a social identity with other crowd members or a crowd in which they did not. Participants subsequently completed measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 60 publications
1
29
0
Order By: Relevance
“…We propose that such false negatives are particularly likely in the context of salient shared group membership, which may attenuate disgust reactions. Recent evidence for this proposition comes from Reicher and colleagues (Reicher, Templeton, Neville, Ferrari, & Drury 2016; see also Khazaie & Khan, 2019). In two studies, these authors found that participants felt less disgust towards a damp sports-shirt that smelled of perspiration when it bore a logo of their own university, compared to when it bore the logo of a rival university.…”
Section: A Role For Disgustmentioning
confidence: 99%
“…We propose that such false negatives are particularly likely in the context of salient shared group membership, which may attenuate disgust reactions. Recent evidence for this proposition comes from Reicher and colleagues (Reicher, Templeton, Neville, Ferrari, & Drury 2016; see also Khazaie & Khan, 2019). In two studies, these authors found that participants felt less disgust towards a damp sports-shirt that smelled of perspiration when it bore a logo of their own university, compared to when it bore the logo of a rival university.…”
Section: A Role For Disgustmentioning
confidence: 99%
“…Once again, research confirms the role of a shared identity in attenuating disgust and motivating such sharing. Hult Khazaie and Khan (2019, Study 2) report data gathered from music festival attendees showing that the perception of a shared identity had an indirect effect on increasing the likelihood of engagement in risky practices (e.g., sharing water bottles) and that this was mediated via decreased disgust. They also found a similar indirect effect of shared identity (again via decreased disgust) on (reducing) the degree to which participants judged themselves vulnerable to infection.…”
Section: Mass Gathering Health: Understanding the Costs And Benefitsmentioning
confidence: 99%
“…Contrary to both Cruwys et al (2020) and Khazaie and Khan (2019), however, the spectators’ lowered risk perception and concern for disease spread did not increase risk-taking, since they did not decrease adherence to COVID-19 safety measures. There are two important caveats to these findings.…”
Section: Perceived Risk Concern For Risk and Risk-takingmentioning
confidence: 79%
“…Khazaie and Khan (2019) explored the effect of social identification on health-risk perceptions, disgust, and likelihood of engaging in risk-taking behaviors. They found that participants asked to imagine being in a psychological crowd were less concerned about disease spread and reported greater likelihood to engage in health-risk behaviors (e.g., providing physical support to someone with flu-like symptoms) compared to those in the physical crowd condition.…”
Section: Perceived Risk Concern For Risk and Risk-takingmentioning
confidence: 99%
See 1 more Smart Citation